Design, Synthesis, and Evaluation of Niclosamide Analogs as Therapeutic Agents for Enzalutamide-Resistant Prostate Cancer - Borui Kang; Madhusoodanan Mottamal; Qiu Zhong; Melyssa Bratton; Changde Zhang; Shanchun Guo; Ahamed Hossain; Peng Ma; Qiang Zhang; Guangdi Wang; Florastina Payton-Stewart (Pharmaceuticals, 2023)
Niclosamide effectively downregulates androgen receptor variants (AR-Vs) for treating enzalutamide and abiraterone-resistant prostate cancer. However, the poor pharmaceutical properties of niclosamide due to its solubility and metabolic instability have limited its clinical utility as a systemic treatment for cancer. A novel series of niclosamide analogs was prepared to systematically explore the structure–activity relationship and identify active AR-Vs inhibitors with improved pharmaceutical properties based on the backbone chemical structure of niclosamide. Compounds were characterized using 1H NMR, 13C NMR, MS, and elemental analysis. The synthesized compounds were evaluated for antiproliferative activity and downregulation of AR and AR-V7 in two enzalutamide-resistant cell lines, LNCaP95 and 22RV1. Several of the niclosamide analogs exhibited equivalent or improved anti-proliferation effects in LNCaP95 and 22RV1 cell lines (B9, IC50 LNCaP95 and 22RV1 = 0.130 and 0.0997 μM, respectively), potent AR-V7 down-regulating activity, and improved metabolic stability. In addition, both a traditional structure–activity relationship (SAR) and 3D-QSAR analysis were performed to guide further structural optimization. The presence of two -CF3 groups of the most active B9 in the sterically favorable field and the presence of the -CN group of the least active B7 in the sterically unfavorable field seem to make B9 more potent than B7 in the antiproliferative activity.